STRATEGI MENINGKATKAN MUTU PENDIDIKAN DI MADRASAH ALIYAH HASAN JUFRI - Muwafiqus Shobri (CENDEKIA: Jurnal Studi Keislaman, 2017)
The writing of this article is motivated by the demands of a quality educational institution that can create quality human resources. Madrasah Aliyah Hasan Jufri, the only Madrassa Aliyah with the largest number of learners in Bawean Island is required for its role to realize that expectation. This research uses descriptive method with qualitative approach. Data is taken through observation, interview and documentation. Respondents consisted of madrasah head, deputy head of madrasah, head of administration, head of library and some teachers. The result of the research shows that the strategy to improve the quality of education in Madrasah Aliyah Hasan Jufri is to improve the quality of teachers, increase academic and non academic achievement, increase the achievement of National Examination score and the achievement of School Exam as well as the improvement of infrastructure facilities. Supporting factors in improving the quality of education are qualified teachers of education S1 and some S2 in accordance with subjects that diampu, madrasah have education programs and clear division of tasks, infrastructure, climate and a conducive environment and great support from Yayasan Pondok Pesantren Hasan Jufri. Inhibiting factors are still low student learning motivation, employee resource has not maximal, low level of teacher discipline and fund availability still less. Efforts made in improving the quality of education are intensifying guidance and counseling activities, creating an exciting learning atmosphere, rewarding outstanding students, involving relevant staff in training activities, and applying an electrical attendance system for teachers and employees.